A critical introduction to the metaphysics of modality - Borghini, Andrea, 1977- (Bloomsbury critical introductions to contemporary metaphysics., 2016)
"A Critical Introduction to the Metaphysics of Modality examines the eight main contemporary theories of possibility behind a central metaphysical topic. Covering modal skepticism, modal expressivism, modalism, modal realism, ersatzism, modal fictionalism, modal agnosticism, and the new modal actualism, this comprehensive introduction to modality places contemporary debates in an historical context. Beginning with a historical overview, Andrea Borghini discusses Parmenides and Zeno; looks at how central Medieval authors such as Aquinas, and Buridan prepared the ground for the Early Modern radical views of Leibniz, Spinoza, and Hume and discusses advancements in semantics in the later-half of the twentieth century a resulted in the rise of modal metaphysics, the branch characterizing the past few decades of philosophical reflection. Framing the debate according to three main perspectives - logical, epistemic, metaphysical- Borghini provides the basic concepts and terms required to discuss modality. With suggestions of further reading and end-of-chapter study questions, A Critical Introduction to the Metaphysics of Modality is an up-to-date resource for students working in contemporary metaphysics seeking a better understanding of this crucial topic."--Bloomsbury Publishing